2017
DOI: 10.1002/cbf.3258
|View full text |Cite
|
Sign up to set email alerts
|

TRPA1 contributed to the neuropathic pain induced by docetaxel treatment

Abstract: Peripheral mechanical neuropathic pain is a serious side effect of docetaxel chemotherapy for cancer. However, the underlying mechanism for this side effect is unknown. In the present study, we found that docetaxel treatment induced mechanical allodynia in rats. We further revealed that the transient receptor potential ankyrin subtype 1 protein (TRPA1) protein level is upregulated and the TRPA1 activator allyl isothiocyanate induced larger ion currents in the dorsal root ganglion neurons from the docetaxel tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…Because we found that Ohmline is acting in active SK3 channel, (9) this strongly suggests that the increased Ca 2þ entry induced by docetaxel is linked to the activity of SK3 channel. This finding is in agreement with the observation that docetaxel and paclitaxel can both activate voltage-independent Ca 2þ channel such as transient receptor potential channels TRPV4 (5), TRPA1 (17), and the voltage-gated Ca 2þ channel (CaV3.2; ref. 6).…”
Section: Discussionsupporting
confidence: 92%
“…Because we found that Ohmline is acting in active SK3 channel, (9) this strongly suggests that the increased Ca 2þ entry induced by docetaxel is linked to the activity of SK3 channel. This finding is in agreement with the observation that docetaxel and paclitaxel can both activate voltage-independent Ca 2þ channel such as transient receptor potential channels TRPV4 (5), TRPA1 (17), and the voltage-gated Ca 2þ channel (CaV3.2; ref. 6).…”
Section: Discussionsupporting
confidence: 92%
“…The first card, used to look for differences between whole DRG and MACS-sorted samples, contained probe sets for a mixture of neuronal and non-neuronal genes known to be present in the DRG that can be activated by NGF and other mediators. These include genes such as TRPVI and TRPA1, ion-channels widely expressed on neuronal cells known to be involved in nociception (Caterina and Julius, 2001;Bevan, Quallo and Andersson, 2014;Huang et al, 2017). In addition, the array card contained probe sets for some cytokine and chemokine genes.…”
Section: Rna Extraction and Taqman Qpcr Array Cardsmentioning
confidence: 99%
“…Another standard model of neuropathic pain is the one induced by the administration of chemotherapy drugs that may produce, as side effects, intense cold and mechanical hyperalgesia and/or allodynia, limiting administration to patients [157,158]. Similar to nerve injury models, the blockage of TRPA1 counteracted pain in several models of chemotherapy-induced neuropathic pain [159,160]. Oxaliplatin is often used to establish experimental neuropathic pain, through TRPA1 [161,162] but not TRPV1 sensitisation [163].…”
Section: Trpa1 In Neuropathic Painmentioning
confidence: 99%